A low-temperature early-strength coagulant for magnesite cementitious materials and its preparation method and use method

By developing a low-temperature premature coagulation agent composed of glacial acetic acid, sodium triflate, aluminum benzoate and other components, the problem of slow reaction speed and low early strength under low temperature conditions was solved, and the early strength and production cost were improved are achieved.

CN116514449BActive Publication Date: 2025-04-15SHANDONG MEIJIATU NEW MATERIAL TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310518535.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-10
Publication Date
2025-04-15
Estimated Expiration
2043-05-10

AI Technical Summary

Technical Problem

Magnesite gelling materials react slowly under low temperature conditions and have low early strength, resulting in long demolding time and long room temperature curing cycle, increasing production costs and energy consumption.

Method used

Develop a low-temperature premature coagulant accelerator for magnesite gelling materials. Through the combination of components such as glacial acetic acid, sodium triflate, aluminum benzoate, dibenzene sorbitol, etc., an effective coagulant is formed to improve the early strength and reaction speed of the material.

Benefits of technology

It significantly improves the early strength and reaction speed of magnesite gelling materials under low temperature conditions, shortens the demolding time and room temperature curing cycle, and reduces production costs and energy consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004220042690000051
    Figure BDA0004220042690000051
Patent Text Reader

Abstract

The invention provides a low-temperature early-strength coagulant for a magnesite cementitious material, a preparation method and a use method. The low-temperature early-strength coagulant consists of the following components in parts by weight: 1.2-4.5 parts of glacial acetic acid, 0.1-4.2 parts of sodium trifluoromethanesulfonate, 1.2-4.0 parts of aluminum benzoate, 0.5-2.5 parts of dibenzylidene sorbitol, 1.5-3.0 parts of 4-ethoxy-4-oxobutyric acid, 0.9-1.5 parts of polyvinyl cyclohexane, 1.3-5.6 parts of amorphous sodium silicate, 2.2-4.5 parts of lauric acid diethanolamide, 1.1-3.3 parts of lauroamidopropyl dimethyl tertiary amine, 0.5-1 parts of an organosilicon waterproofing agent, 20-35 parts of ethanol and 35-50 parts of water. After being added as an external additive to the cementitious material, it can effectively shorten the coagulation time of the magnesia slurry under low temperature conditions, improve the early and late strength of the product, shorten the demoulding time, improve production efficiency, reduce energy loss, and solve the problem of brine return.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of magnesite cementitious material modifiers, and in particular relates to a low-temperature early-strength coagulant for magnesite cementitious materials and a preparation method and a use method thereof. Background Art

[0002] Cement is one of the most important materials in construction and road engineering. As an inorganic cementitious material, it can solidify from a fluid slurry into a stone-like body with high mechanical strength through a hydration reaction. Unlike traditional hydraulic cementitious materials such as silicate cement, ferroaluminate cement, and sulphoaluminate cement, magnesia cement, also known as magnesia cement, is an air-hardening cementitious material that can only be hydrated in the air and maintain strength development. Due to its excellent mechanical properties, fast setting speed, strong bonding force, smooth and beautiful surface, flame retardant and heat insulation performance characteristics, it is widely used in construction engineering, transportation engineering, decorative materials and refractory products, and has broad prospects in replacing steel and wood. my country is the country with the richest magnesium resources in the world. At the same time, the production process of magnesia cement is relatively simple and the production process has low energy consumption. When preparing magnesium cement products, it can also be used together with industrial and agricultural wastes such as plant straw, sawdust, fly ash, slag, and silica fume to play a role in waste recycling. However, this material can only react normally under the temperature condition of 20-35℃. The reaction speed is slow below 15℃, the early strength is low, the demoulding time is long, and the room temperature curing cycle is long. At present, in order to solve the demoulding problem, a greenhouse constant temperature and humidity curing scheme is adopted, which increases production costs and energy consumption. Therefore, the development of a low-temperature early strength accelerator is a key issue that needs to be solved in the development of magnesite cement.

[0003] The Chinese invention patent application with publication number CN1477076A discloses a "method for preparing a low-temperature early-strength coagulant for Lingmei cementitious materials". Its technical solution is to use 25-35% NaOH solution, 15%-25% neutralizer, 20%-30% chlorinated acid, and 20%-30% water as raw materials, add the above raw materials into a reactor after being measured in percentage, stir for 100-150 minutes at 80-95°C, and then take out and can it. However, its disadvantage is that it can only improve the 1d strength. Summary of the invention

[0004] The invention provides a low-temperature early-strength coagulant for magnesite cementitious materials, a preparation method and a use method thereof, to solve the above-mentioned technical problems.

[0005] The technical solution of the present invention is achieved in this way:

[0006] A low-temperature early-strength coagulant for magnesite cementitious materials, comprising the following components in parts by weight:

[0007] 1.2-4.5 parts of glacial acetic acid, 0.1-4.2 parts of sodium trifluoromethanesulfonate, 1.2-4.0 parts of aluminum benzoate, 0.5-2.5 parts of dibenzylidene sorbitol, 1.5-3.0 parts of 4-ethoxy-4-oxobutyric acid, 0.9-1.5 parts of polyvinyl cyclohexane, 1.3-5.6 parts of amorphous sodium silicate, 2.2-4.5 parts of lauric acid diethanolamide, 1.1-3.3 parts of lauryl amide propyl dimethyl tertiary amine, 0.5-1 parts of silicone waterproofing agent, 20-35 parts of ethanol, and 35-50 parts of water.

[0008] Furthermore, the organic silicon waterproofing agent is any one of methyl silicic acid, sodium methyl silicate and potassium methyl silicate.

[0009] Further, 2.5 parts of glacial acetic acid, 3.5 parts of sodium trifluoromethanesulfonate, 3.0 parts of aluminum benzoate, 1.7 parts of dibenzylidene sorbitol, 1.6 parts of 4-ethoxy-4-oxobutyric acid, 1.2 parts of polyvinyl cyclohexane, 4.5 parts of amorphous sodium silicate, 3.0 parts of lauric acid diethanolamide, 2.3 parts of lauryl amide propyl dimethyl tertiary amine, 0.7 parts of sodium methyl silicate, 30 parts of ethanol, and 46 parts of water.

[0010] Furthermore: the organic silicon waterproofing agent is potassium methyl silicate, and the weight portion of potassium methyl silicate is 0.5-0.7 parts.

[0011] A method for preparing a low-temperature early-strength coagulant for magnesite cementitious materials comprises the following steps:

[0012] (1) According to any one of the above-mentioned formulas of low-temperature early-strength setting accelerators for magnesite cementitious materials, glacial acetic acid, sodium trifluoromethanesulfonate, aluminum benzoate, dibenzylidene sorbitol, 4-ethoxy-4-oxobutyric acid, polyvinyl cyclohexane, amorphous sodium silicate, lauric acid diethanolamide, lauroyl amide propyl dimethyl tertiary amine, silicone waterproofing agent, ethanol and water are weighed respectively.

[0013] (2) sodium trifluoromethanesulfonate, aluminum benzoate, dibenzylidene sorbitol, 4-ethoxy-4-oxobutyric acid, and ethanol in step (1) are added to a reaction kettle in sequence and mixed evenly, and heating and stirring are started until sodium trifluoromethanesulfonate, aluminum benzoate, and dibenzylidene sorbitol are completely dissolved, and glacial acetic acid, polyvinyl cyclohexane, lauric acid diethanolamide, and lauroylamidopropyl dimethyl tertiary amine in step (1) are slowly added to the reaction kettle in sequence at a flow rate of 20 mL / min using a constant flow pump, and mixed and stirred evenly to obtain a mixed organic solution.

[0014] (3) The amorphous sodium silicate weighed in step (1) and water are mixed and stirred at 20-25° C. to obtain a mixed aqueous solution, and the organosilicon waterproofing agent weighed in step (1) is slowly added thereto under stirring to obtain a uniform mixed aqueous solution after stirring.

[0015] (4) Mixing the mixed organic solution obtained in step (2) and the mixed aqueous solution obtained in step (3) at 20-25° C. and stirring evenly to obtain a magnesite cement material accelerator.

[0016] Furthermore, in step (2), the sodium trifluoromethanesulfonate, aluminum benzoate, dibenzylidene sorbitol, 4-ethoxy-4-oxobutyric acid and ethanol are mixed and stirred at a temperature of 28-32° C., and glacial acetic acid, polyvinyl cyclohexane, lauric acid diethanolamide and lauroylamidopropyl dimethyl tertiary amine are added in sequence at a flow rate of 20 mL / min using a constant flow pump while maintaining the temperature, and then mixed and stirred for 60-90 minutes.

[0017] The present invention also discloses a method for using a low-temperature early-strength coagulant for magnesite cementitious materials, specifically: the addition amount of the low-temperature early-strength coagulant is 0.5wt%-1.5wt% of the magnesite cementitious materials (magnesite cement raw materials).

[0018] As a further technical solution of the above method of use: the low-temperature early-strength coagulant for magnesite cementitious material is added into the magnesite slurry at a flow rate of 40-60 mL / min by a constant flow pump and mixed evenly for use.

[0019] Compared with the prior art, the working principle and beneficial effects of the present invention are as follows:

[0020] 1. In the technical solution of the present invention, the surface reaction process of the magnesia gel material is studied. Initially, MgO is dissolved in the regulator solution to react and generate Mg(OH)2 and gradually begin to dissociate. At the same time, Mgcl2 is ionized in the liquid to generate hydrated magnesium oxychloride cationic complex, OH - and cl - Plasma, in this process, glacial acetic acid and sodium trifluoromethanesulfonate can effectively induce the formation of magnesium oxychloride cationic complex after compounding, under this condition, dissolution and hydrolysis reactions continue. The second is the crystallization stage. After the solution concentration reaches a certain level due to the continuous dissolution and hydrolysis, the hydrated magnesium oxychloride cationic complex will undergo a condensation reaction under the joint initiation of aluminum benzoate, dibenzylidene sorbitol, and 4-ethoxy-4-oxobutyric acid to form colloidal particles of the product phase (5.1.8 phase (5Mg(OH)2.Mgcl2.8H2O) and (3Mg(OH)2.Mgcl2.8H2O) and release heat. This process consumes a large amount of free water, causing the magnesium cement paste to lose fluidity and become gel-like, and gradually precipitate fibrous crystals. Lauric acid diethanolamide and lauroyl amide propyl dimethyl tertiary amine accelerate crystal formation and optimize the crystal lap structure. The crystals are interlaced and filled between the unhydrated particles, and finally form 3-phase and 5-phase dense stacking, which hardens the paste and the strength continues to increase.

[0021] 2. In the technical scheme of the present invention, after the organosilicon waterproofing agent is mixed into the magnesite slurry, the hydrophilic group faces the magnesite cement, and the hydrophobic group is evenly arranged around the pores to form a hydrophobic "wall", which prevents water from infiltrating. At the same time, it forms a stable complex with cations such as magnesium and calcium in the magnesite cement, making the needle-shaped 518 crystal phase smaller, and the waterproofing agent is more closely combined with the magnesite cement, reducing the dissolution and damage of water, increasing the water resistance of the product, and forming a layer of colorless, transparent, UV-resistant breathable film that is not noticeable to the naked eye on the surface of the magnesite product. When rain water blows on it or meets humid air, water droplets will flow naturally, preventing water from invading, thereby having a certain inhibitory effect on the return of halogen in the later stage of magnesite cementing material. Water and ethanol are used as medium to promote the raw materials to be evenly dispersed in the medium to form a uniform and stable mixed solution. Finally, adding sodium silicate can increase the viscosity of the mixed solution to a limited extent, facilitate post-production, be convenient for transportation and use, and can be stored at room temperature.

[0022] 3. This process is highly environmentally friendly, has a mild reaction temperature, generates no waste, has low cost, and has high promotion value. DETAILED DESCRIPTION

[0023] The following examples are used to illustrate the present invention but are not intended to limit the scope of the present invention. Without departing from the spirit and essence of the present invention, modifications and substitutions made to the steps, methods or conditions of the present invention all fall within the scope of the present invention.

[0024] Unless otherwise specified, the technical means used in the examples are conventional means well known to those skilled in the art.

[0025] The present invention provides a low-temperature early-strength coagulant for magnesite cementitious materials and a preparation method thereof, and specific embodiments thereof are as follows:

[0026] Example 1

[0027] (1) Weigh 2.5 parts of glacial acetic acid, 3.5 parts of sodium trifluoromethanesulfonate, 3.0 parts of aluminum benzoate, 1.7 parts of dibenzylidene sorbitol, 1.6 parts of 4-ethoxy-4-oxobutyric acid, 1.2 parts of polyvinyl cyclohexane, 4.5 parts of amorphous sodium silicate, 3.0 parts of lauric acid diethanolamide, 2.3 parts of lauroamidopropyl dimethyl tertiary amine, 0.7 parts of sodium methyl silicate, 30 parts of ethanol, and 46 parts of water.

[0028] (2) Sodium trifluoromethanesulfonate, aluminum benzoate, dibenzylidene sorbitol, 4-ethoxy-4-oxobutyric acid, and ethanol in step (1) are sequentially added to a reaction kettle and mixed evenly, heated to 30° C. and stirred until all solids are completely dissolved, and then glacial acetic acid, polyvinyl cyclohexane, lauric acid diethanolamide, and lauroylamidopropyl dimethyl tertiary amine in step (1) are slowly added to the reaction kettle at a flow rate of 20 mL / min using a constant flow pump, and the mixture is stirred for 60 min to obtain a mixed organic solution.

[0029] (3) The amorphous sodium silicate and water weighed in step (1) are mixed and stirred at preferably 20° C. (the mixing and stirring temperature may also be 25° C., 23° C., etc., as long as it is between 20 and 25° C.) to obtain a mixed aqueous solution, and the organosilicon waterproofing agent weighed in step (1) is added at a flow rate of 20 mL / min using a constant flow pump under stirring conditions, and a uniform mixed aqueous solution is obtained after stirring.

[0030] (4) Mix the mixed organic solution obtained in step (2) and the mixed aqueous solution obtained in step (3) at 25°C (the mixing and stirring temperature can also be 20°C, 23°C, etc., as long as it is between 20 and 25°C), and stir evenly to obtain a magnesite cement material accelerator.

[0031] Example 2

[0032] Weigh 2.0 parts of glacial acetic acid, 4.0 parts of sodium trifluoromethanesulfonate, 1.5 parts of aluminum benzoate, 1.5 parts of dibenzylidene sorbitol, 3.0 parts of 4-ethoxy-4-oxobutyric acid, 1.0 part of polyvinyl cyclohexane, 5.0 parts of amorphous sodium silicate, 4.2 parts of lauric acid diethanolamide, 3.3 parts of lauroamidopropyl dimethyl tertiary amine, 1.0 part of potassium methyl silicate, 30.5 parts of ethanol, and 43 parts of water. Other steps are the same as in Example 1.

[0033] Example 3

[0034] Weigh 1.2 parts of glacial acetic acid, 4.2 parts of sodium trifluoromethanesulfonate, 1.6 parts of aluminum benzoate, 2.5 parts of dibenzylidene sorbitol, 1.5 parts of 4-ethoxy-4-oxobutyric acid, 1.5 parts of polyvinyl cyclohexane, 4.5 parts of amorphous sodium silicate, 2.2 parts of lauric acid diethanolamide, 3.3 parts of lauroylamidopropyl dimethyl tertiary amine, 0.5 parts of silicone waterproofing agent, 35 parts of ethanol, and 42 parts of water. The other steps of the preparation method are the same as those in Example 1.

[0035] The above Examples 1-3 are respectively used in the production of magnesite products of the present invention, which are Application Examples 1-3. In the application examples, the specific addition amount of the above magnesite product modifier is shown in Table 1 below.

[0036] Among them, the application method (taking the flat mold production of magnesium oxychloride door core board and room temperature of 10℃ as an example) is:

[0037] Raw material ratio: light-burned magnesium oxide powder (activity 65) 100kg, magnesium chloride solution (30°Bé) 110kg, fiber (pp staple fiber) 1.5kg, foaming agent (composite foaming agent): 0.7kg, foaming liquid (foaming agent: water = 1:80), low-temperature early strength accelerator is added according to the proportion in the table below.

[0038] Production process: prepare the magnesium chloride solution one day in advance, measure the amount of light-burned magnesium oxide powder, magnesium chloride solution, fiber, foaming agent, water for diluting the foaming agent, and low-temperature early strength accelerator according to the production formula and the capacity of the mixer, add the water for diluting the foaming agent to the weighed foaming agent to prepare the foaming liquid. Put the measured light-burned magnesium oxide powder, magnesium chloride solution and fiber into the mixer in turn, stir evenly at high speed, and prepare magnesium oxychloride cement slurry (magnesite cement slurry includes magnesium oxychloride, magnesium oxysulfide, sulfur-chlorine composite and magnesium phosphate. Magnesium phosphate reacts quickly and does not need to be accelerated, while the rest need to be accelerated, and magnesium oxychloride has the best strength.), magnesium oxychloride slurry is composed of magnesium chloride solution and light-burned magnesium oxide powder; the addition amount of low-temperature early strength coagulant is 0.5wt%-1.5wt% of magnesite cementitious material (magnesite cement raw material), and the low-temperature early strength coagulant is added to the magnesite cement slurry in this proportion, and a constant flow pump is used to add it at a flow rate of 40-60mL / min, stir evenly, start the foaming machine, and foam the foaming liquid into foam through the foaming machine, add the foam into the mixer and stir and mix thoroughly to form a uniform slurry, and send the prepared slurry into the molding machine or mold. After the surface is scraped flat, the template is ferried to the curing area with the ferry. After solidification, the mold is opened and the board is removed.

[0039] The accelerating effects and performance parameters of implementation case 1, implementation case 2 and implementation case 3 are shown in Table 1.

[0040] Table 1: Amount of coagulant used, coagulant effect and performance parameters in application examples

[0041]

[0042]

[0043] It can be seen from the data in Table 1 that the coagulants of Example 1, Example 2 and Example 3 have good accelerating effects when applied to magnesium oxysulfate cement products, and also have excellent early and late strength properties, anti-halogenation properties, and are easy to industrialize.

[0044] The present invention provides a low-temperature early-strength coagulant for magnesite cementitious materials and a preparation method thereof. In addition to the above-mentioned embodiments 1 to 3, there are also the following embodiments:

[0045] Example 4

[0046] Weigh 4.5 parts of glacial acetic acid, 0.3 parts of sodium trifluoromethanesulfonate, 1.5 parts of aluminum benzoate, 1.5 parts of dibenzylidene sorbitol, 2 parts of 4-ethoxy-4-oxobutyric acid, 1.1 parts of polyvinyl cyclohexane, 2.7 parts of amorphous sodium silicate, 2.5 parts of lauric acid diethanolamide, 2.3 parts of lauroyl amide propyl dimethyl tertiary amine, 0.6 parts of silicone waterproofing agent, 30 parts of ethanol, and 40 parts of water. The other steps of the preparation method are the same as those in Example 1.

[0047] Example 5

[0048] Weigh 1.5 parts of glacial acetic acid, 0.1 parts of sodium trifluoromethanesulfonate, 2 parts of aluminum benzoate, 1 part of dibenzylidene sorbitol, 2.5 parts of 4-ethoxy-4-oxobutyric acid, 1.2 parts of polyvinyl cyclohexane, 4.8 parts of amorphous sodium silicate, 3 parts of lauric acid diethanolamide, 1.9 parts of lauroamidopropyl dimethyl tertiary amine, 0.7 parts of organosilicon waterproofing agent, 25 parts of ethanol, and 38 parts of water. The other steps of the preparation method are the same as those in Example 1.

[0049] Example 6

[0050] Weigh 2 parts of glacial acetic acid, 0.9 parts of sodium trifluoromethanesulfonate, 1.2 parts of aluminum benzoate, 0.9 parts of dibenzylidene sorbitol, 2.8 parts of 4-ethoxy-4-oxobutyric acid, 1 part of polyvinyl cyclohexane, 1.9 parts of amorphous sodium silicate, 3.5 parts of lauric acid diethanolamide, 2.1 parts of lauroamidopropyl dimethyl tertiary amine, 0.9 parts of organosilicon waterproofing agent, 21 parts of ethanol, and 39 parts of water. The other steps of the preparation method are the same as those in Example 1.

[0051] Example 7

[0052] Weigh 2.6 parts of glacial acetic acid, 1.6 parts of sodium trifluoromethanesulfonate, 4.0 parts of aluminum benzoate, 1.3 parts of dibenzylidene sorbitol, 2.1 parts of 4-ethoxy-4-oxobutyric acid, 1.3 parts of polyvinyl cyclohexane, 4.6 parts of amorphous sodium silicate, 3.8 parts of lauric acid diethanolamide, 3.2 parts of lauroyl amide propyl dimethyl tertiary amine, 0.9 parts of silicone waterproofing agent, 32 parts of ethanol, and 46 parts of water. The other steps of the preparation method are the same as those in Example 1.

[0053] Example 8

[0054] Weigh 4.3 parts of glacial acetic acid, 4.1 parts of sodium trifluoromethanesulfonate, 3.9 parts of aluminum benzoate, 0.5 parts of dibenzylidene sorbitol, 2.8 parts of 4-ethoxy-4-oxobutyric acid, 1.4 parts of polyvinyl cyclohexane, 5.5 parts of amorphous sodium silicate, 2.3 parts of lauric acid diethanolamide, 3.2 parts of lauroamidopropyl dimethyl tertiary amine, 0.9 parts of silicone waterproofing agent, 33 parts of ethanol, and 41 parts of water. The other steps of the preparation method are the same as those in Example 1.

[0055] Example 9

[0056] Weigh 3.9 parts of glacial acetic acid, 3.2 parts of sodium trifluoromethanesulfonate, 2.5 parts of aluminum benzoate, 2.5 parts of dibenzylidene sorbitol, 2.6 parts of 4-ethoxy-4-oxobutyric acid, 1.3 parts of polyvinyl cyclohexane, 4.5 parts of amorphous sodium silicate, 3.2 parts of lauric acid diethanolamide, 2.3 parts of lauroyl amide propyl dimethyl tertiary amine, 0.8 parts of silicone waterproofing agent, 31 parts of ethanol, and 42 parts of water. The other steps of the preparation method are the same as those in Example 1.

[0057] Example 10

[0058] Weigh 1.3 parts of glacial acetic acid, 0.2 parts of sodium trifluoromethanesulfonate, 1.3 parts of aluminum benzoate, 0.6 parts of dibenzylidene sorbitol, 3.0 parts of 4-ethoxy-4-oxobutyric acid, 1 part of polyvinyl cyclohexane, 1.4 parts of amorphous sodium silicate, 4.4 parts of lauric acid diethanolamide, 1.2 parts of lauroyl amide propyl dimethyl tertiary amine, 0.9 parts of silicone waterproofing agent, 27 parts of ethanol, and 46 parts of water. The other steps of the preparation method are the same as those in Example 1.

[0059] Embodiment 11

[0060] Weigh 4 parts of glacial acetic acid, 2.8 parts of sodium trifluoromethanesulfonate, 1.5 parts of aluminum benzoate, 1.4 parts of dibenzylidene sorbitol, 1.7 parts of 4-ethoxy-4-oxobutyric acid, 0.9 parts of polyvinyl cyclohexane, 1.3 parts of amorphous sodium silicate, 2.5 parts of lauric acid diethanolamide, 1.4 parts of lauroyl amide propyl dimethyl tertiary amine, 0.6 parts of silicone waterproofing agent, 29 parts of ethanol, and 35 parts of water. The other steps of the preparation method are the same as those in Example 1.

[0061] Example 12

[0062] Weigh 1.9 parts of glacial acetic acid, 4 parts of sodium trifluoromethanesulfonate, 3.8 parts of aluminum benzoate, 0.6 parts of dibenzylidene sorbitol, 1.9 parts of 4-ethoxy-4-oxobutyric acid, 1.2 parts of polyvinyl cyclohexane, 5.6 parts of amorphous sodium silicate, 4.5 parts of lauric acid diethanolamide, 1.1 parts of lauroamidopropyl dimethyl tertiary amine, 0.9 parts of silicone waterproofing agent, 33 parts of ethanol, and 50 parts of water. The other steps of the preparation method are the same as those in Example 1.

[0063] The low-temperature early-strength coagulant for magnesite cementitious materials prepared in the above embodiment can also solve the technical problems described in the prior art. The dry density and anti-halogen reversion after use are the same as those in Table 1, respectively.

[0064] When used specifically:

[0065] Example 4, dosage 1.4%, demoulding time 380min, 28-day flexural strength 0.48, 28-day compressive strength 0.76;

[0066] Example 5, dosage 0.6%, demoulding time 610min, 28-day flexural strength 0.38, 28-day compressive strength 0.63;

[0067] Example 6, dosage 0.7%, demoulding time 570min, 28-day flexural strength 0.40, 28-day compressive strength 0.67;

[0068] Example 7, dosage 0.8%, demoulding time 550min, 28-day flexural strength 0.39, 28-day compressive strength 0.71;

[0069] Example 8, dosage 0.9%, demoulding time 535min, 28-day flexural strength 0.44, 28-day compressive strength 0.73;

[0070] Example 9, dosage 1.0%, demoulding time 493min, 28-day flexural strength 0.43, 28-day compressive strength 0.72;

[0071] Example 10, dosage 1.1%, demoulding time 490min, 28-day flexural strength 0.39, 28-day compressive strength 0.71;

[0072] Example 11, dosage 1.2%, demoulding time 450min, 28-day flexural strength 0.40, 28-day compressive strength 0.70;

[0073] Example 12, dosage 1.3%, demoulding time 505min, 28-day flexural strength 0.40, 28-day compressive strength 0.77.

[0074] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to illustrate all the embodiments here. However, obvious changes or modifications derived from this solution are still within the scope of protection of the present invention.

Claims

1. A low-temperature early-strength coagulant for magnesite cementitious materials, characterized in that: It is composed of the following components in parts by weight: 1.2-4.5 parts of glacial acetic acid, 0.1-4.2 parts of sodium trifluoromethanesulfonate, 1.2-4.0 parts of aluminum benzoate, 0.5-2.5 parts of dibenzylidene sorbitol, 1.5-3.0 parts of 4-ethoxy-4-oxobutyric acid, 0.9-1.5 parts of polyvinyl cyclohexane, 1.3-5.6 parts of amorphous sodium silicate, 2.2-4.5 parts of lauric acid diethanolamide, 1.1-3.3 parts of lauryl amide propyl dimethyl tertiary amine, 0.5-1 parts of silicone waterproofing agent, 20-35 parts of ethanol, and 35-50 parts of water.

2. The low-temperature early-strength coagulant for magnesite cementitious materials according to claim 1, characterized in that: The organic silicon waterproofing agent is any one of methyl silicic acid, sodium methyl silicate and potassium methyl silicate.

3. The low-temperature early-strength coagulant for magnesite cementitious materials according to claim 2, characterized in that: It is composed of the following components in parts by weight: 2.5 parts of glacial acetic acid, 3.5 parts of sodium trifluoromethanesulfonate, 3.0 parts of aluminum benzoate, 1.7 parts of dibenzylidene sorbitol, 1.6 parts of 4-ethoxy-4-oxobutyric acid, 1.2 parts of polyvinyl cyclohexane, 4.5 parts of amorphous sodium silicate, 3.0 parts of lauric acid diethanolamide, 2.3 parts of lauryl amide propyl dimethyl tertiary amine, 0.7 parts of sodium methyl silicate, 30 parts of ethanol, and 46 parts of water.

4. The low-temperature early-strength coagulant for magnesia cementitious materials according to claim 2, characterized in that: The organic silicon waterproofing agent is potassium methyl silicate, and the weight portion of potassium methyl silicate is 0.5-0.7 parts.

5. A method for preparing a low-temperature early-strength coagulant for magnesite cementitious materials, characterized in that: The following steps are involved: (1) According to the formula of the low-temperature early strength coagulant for magnesia cementitious material as claimed in any one of claims 1 to 4, glacial acetic acid, sodium trifluoromethanesulfonate, aluminum benzoate, dibenzylidene sorbitol, 4-ethoxy-4-oxobutyric acid, polyvinyl cyclohexane, amorphous sodium silicate, lauric acid diethanolamide, lauroyl amide propyl dimethyl tertiary amine, silicone waterproofing agent, ethanol and water are weighed respectively; (2) sodium trifluoromethanesulfonate, aluminum benzoate, dibenzylidene sorbitol, 4-ethoxy-4-oxobutyric acid, and ethanol in step (1) are added to a reaction kettle in sequence and mixed evenly, and heating and stirring are started until sodium trifluoromethanesulfonate, aluminum benzoate, and dibenzylidene sorbitol are completely dissolved, and glacial acetic acid, polyvinyl cyclohexane, lauric acid diethanolamide, and lauroylamidopropyl dimethyl tertiary amine in step (1) are added to the reaction kettle in sequence at a flow rate of 20 mL / min using a constant flow pump, and mixed and stirred evenly to obtain a mixed organic solution; (3) mixing the amorphous sodium silicate weighed in step (1) and water at room temperature to obtain a mixed aqueous solution, and adding the organosilicon waterproofing agent weighed in step (1) to the mixed aqueous solution under stirring conditions to obtain a uniform mixed aqueous solution after stirring; (4) The mixed organic solution obtained in step (2) and the mixed aqueous solution obtained in step (3) are mixed at room temperature and stirred evenly to obtain a magnesite cement material accelerator.

6. The method for preparing a low-temperature early-strength coagulant for magnesite cementitious materials according to claim 5, characterized in that: In step (2), the sodium trifluoromethanesulfonate, aluminum benzoate, dibenzylidene sorbitol, 4-ethoxy-4-oxobutyric acid and ethanol are mixed and stirred at a temperature of 28-32° C., and glacial acetic acid, polyvinyl cyclohexane, lauric acid diethanolamide and lauroylamidopropyl dimethyl tertiary amine are sequentially delivered at a flow rate of 20 mL / min using a constant flow pump while maintaining the temperature, and then mixed and stirred for 60-90 minutes.

7. The method for using the low-temperature early-strength coagulant for magnesia cementitious materials according to claim 1, characterized in that: The addition amount of the low-temperature early strength accelerator is 0.5wt%-1.5wt% of the magnesite cementitious material.

8. The method for using a low-temperature early-strength coagulant for magnesia cementitious materials according to claim 7, characterized in that: The low-temperature early-strength coagulant for magnesite cementitious materials is added into the magnesite slurry at a flow rate of 40-60 mL / min by a constant flow pump and mixed evenly for use.

Citation Information

Patent Citations

  • Preparation method of low-temp, early-strength accelerant by uxing magnesite gelation material

    CN1477076A

  • Magnesium oxychloride cement suitable for being used in winter and preparation method thereof

    CN105347773A

  • Prepn of water-reducing and surface halide accumulation resisting modifier for magnesite binding material

    CN1337371A